Plastic scintillation fiber and its manufacturing method
Patent Information
- Application Number
- JP2022550362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-16
- Filing Date
- 2021-07-01
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-01
AI Technical Summary
【0030】 本発明により、従来のシンチレーションファイバよりも高い感度で中性子線を検出可能であって、生産性に優れたプラスチックシンチレーションファイバを提供できる。
Smart Images

Figure 0007645894000001 
Figure 0007645894000002 
Figure 0007645894000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plastic scintillation fiber and a method for producing the same. [Background technology]
[0002] Conventional plastic scintillating fibers (PSFs) are plastic fibers in which the outer surface of the scintillator core is covered with a cladding layer with a lower refractive index than the core, and are primarily used for radiation detection. The core is usually made of a polymeric material in which an organic phosphor is added to a base material having an aromatic ring, such as polystyrene or polyvinyltoluene. The cladding layer is made of a polymeric material with a low refractive index, such as polymethyl methacrylate or fluorine-containing polymethyl methacrylate.
[0003] The principle of radiation detection using plastic scintillation fiber is explained below. The core substrate of scintillation fiber has aromatic rings, and when irradiated radiation crosses the scintillation fiber, it absorbs part of the energy due to re-emission of secondary particles in the core, and emits it as ultraviolet light. If no phosphor is added to the core substrate, this ultraviolet light is absorbed by the core substrate itself and disappears without being transmitted within the core.
[0004] In plastic scintillation fibers, this ultraviolet light is absorbed by the phosphor added to the core substrate, and light of longer wavelengths is re-emitted. Therefore, by selecting an appropriate phosphor, the light can be converted to light of longer wavelengths, such as blue light, which is less likely to be absorbed by the core substrate, and transmitted through the fiber. The light transmitted through the fiber is detected by a detector connected to one or both ends.
[0005] Thus, scintillation fibers have two functions, emitting light by detecting radiation and transmitting light, and are used in applications such as calculating the position and amount of radiation that has passed through. In such scintillation fibers, it is important to efficiently convert the ultraviolet light emitted from the core to a long wavelength and transmit it over long distances.
[0006] On the other hand, plastic wavelength conversion fiber (WLSF: Wavelength Shifting Fiber) is also widely used along with scintillation fiber. Wavelength conversion fiber is used in combination with, for example, a plastic scintillator that emits blue light. A groove or hole is made in a plate-shaped or rod-shaped plastic scintillator, and a wavelength conversion fiber that absorbs blue light and converts it to green light is embedded in it.
[0007] In large-scale, large-area detectors, it can be difficult to transmit light from individual scintillators to an external photoelectric detector (such as a photomultiplier tube) located at a distance due to light attenuation and spatial constraints. In such cases, wavelength conversion fibers that are thin, easy to bend, and capable of long-distance transmission are preferably used. Many wavelength conversion fibers can be freely laid out to the external photoelectric detector.
[0008] The core of the wavelength conversion fiber is made of polystyrene resin or polymethyl methacrylate resin, and a phosphor for wavelength conversion is dissolved in it. In the wavelength conversion fiber, the scintillation light incident from the external scintillator is absorbed by the phosphor in the core, and the light is efficiently wavelength converted and transmitted within the fiber. The scintillator to be combined with the wavelength conversion fiber is not limited to a plastic scintillator, but inorganic scintillators that are highly sensitive to neutrons, etc., can also be used.
[0009] In this way, the wavelength conversion fiber can easily collect the scintillation light emitted from a large-area or long scintillator, or a special scintillator for neutron detection, etc. Also, the wavelength conversion fiber can transmit light whose wavelength has been converted in the core and can be freely connected to a photoelectric detector.
[0010] Here, since it is difficult to detect neutron rays using a plastic scintillator made only of plastic, due to its low sensitivity, an inorganic scintillator is used. Examples of inorganic scintillators include those disclosed in Patent Document 1, LiF / ZnS:Ag, LiI:Eu 2+ , LiBaF3:Ce 3+ , LiCaAlF6:Ce 3+ , Li2B4O7:Cu + Many such as are known.
[0011] However, inorganic scintillators are not very transparent, with an attenuation length of several mm, and cannot transmit the emitted light (i.e., scintillation light) over long distances. In addition, there are restrictions on the crystal size, making it difficult to transmit light to a photoelectric detector using inorganic scintillators.
[0012] Furthermore, as disclosed in Patent Documents 2 and 3, etc., a sheet in which fine particles obtained by crushing an inorganic scintillator are dispersed in a transparent resin has been developed for neutron detection. In such a sheet, the difference in refractive index between the inorganic scintillator and the transparent resin is large, so transparency cannot be ensured and the sheet itself cannot efficiently transmit light to a photoelectric detector.
[0013] For this reason, in Patent Documents 2, 3, 4, etc., a wavelength conversion fiber is arranged along the end face or surface of a scintillator, and the light is transmitted to a photoelectric detector through the wavelength conversion fiber. By using a wavelength conversion fiber, the detection light can be transmitted over a longer distance. Here, in all of Patent Documents 2, 3, and 4, detection that places importance on spatial resolution, such as the image detection disclosed in Patent Document 3 in particular, requires a lot of post-processing to combine the scintillator and the wavelength conversion fiber. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2012-126854 A [Patent Document 2] International Publication No. 2015 / 064588 [Patent Document 3] JP 2011-141239 A [Patent Document 4] JP 2015-72227 A Summary of the Invention [Problem to be solved by the invention]
[0015] In conventional plastic scintillation fibers, the core itself emits scintillation light and transmits the light to the photoelectric detector, so the core must be highly transparent. Therefore, it is not possible to obtain a plastic scintillation fiber for detecting neutron rays by including in the core a material that emits scintillation light when irradiated with neutron rays.
[0016] Similarly, in wavelength conversion fibers, the core is required to have high transparency in order to convert the wavelength of the scintillation light irradiated from an external scintillator and transmit it. Therefore, it is not possible to obtain a plastic scintillation fiber for detecting neutron rays by including in the core a material that emits scintillation light when irradiated with neutron rays.
[0017] On the other hand, conventional scintillation detectors using wavelength conversion fibers require post-processing to combine the scintillator and the wavelength conversion fiber. Furthermore, when detecting images, it is necessary to separate and combine each scintillator for each of the many wavelength conversion fibers, which makes the processing extremely difficult.
[0018] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a plastic scintillation fiber that is capable of detecting neutron rays and has excellent productivity. [Means for solving the problem]
[0019] A plastic scintillation fiber according to one aspect of the present invention comprises: an outermost layer including a plastic material that contains an organic compound including an element having a neutron reaction cross section larger than that of hydrogen and that emits scintillation light when irradiated with a neutron beam; a high refractive index core provided inside the outermost layer and including at least one type of phosphor that absorbs the scintillation light and converts it to a longer wavelength; a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core; The wavelength conversion fiber including the core and the cladding layer and the outermost layer covering the outer peripheral surface of the wavelength conversion fiber are integrally formed.
[0020] In the plastic scintillation fiber of the present invention, the outermost layer contains a plastic material that contains an organic compound containing an element with a neutron reaction cross section larger than that of hydrogen and emits scintillation light when irradiated with a neutron beam, thereby improving the sensitivity to neutrons compared to ordinary plastic scintillation fibers. When irradiated with neutrons, elements such as lithium-6, boron-10, and gadolinium, which have a larger neutron reaction cross section than hydrogen, emit much more radiation than elements such as carbon, oxygen, and hydrogen that constitute ordinary plastic scintillators. In the plastic scintillation fiber of the present invention, such radiation is generated in the plastic material that constitutes the outermost layer, and scintillation light is generated by the radiation. This mechanism allows neutron radiation to be detected with high sensitivity. In addition, since the outermost layer does not require high transparency required for transmitting light like the core, the organic compound can be added in high concentration.
[0021] In addition, in the plastic scintillation fiber according to one aspect of the present invention, the internal core absorbs the scintillation light emitted from the outermost layer, converts the wavelength, and transmits the light. Therefore, it is possible to detect neutron rays, which are difficult to detect due to the low sensitivity of conventional plastic scintillation fibers. In addition, since the wavelength conversion fiber including the core and cladding layer and the outermost layer covering the outer surface of the wavelength conversion fiber are integrally formed, the post-processing of combining the scintillator and the wavelength conversion fiber, which was previously required, is not necessary. In other words, it is possible to provide a plastic scintillation fiber that is capable of detecting neutron rays and has excellent productivity.
[0022] The outermost layer may contain at least one type of phosphor that absorbs the scintillation light and converts it to a longer wavelength.
[0023] The organic compound may include lithium 6. Alternatively, the organic compound may contain boron-10. Here, the organic compound may be a carborane compound. A carborane compound has a high ratio of boron in its molecular weight, and can efficiently add boron-10 atoms. Furthermore, the ratio of boron in the molecular weight of the organic compound may be 50% or more. With this configuration, boron-10 can be contained at a high concentration, and neutron reactivity is increased. Alternatively, the organic compound may include gadolinium.
[0024] The wavelength conversion fiber and the outermost layer may be integrally formed by a drawing process, which further improves productivity.
[0025] A protective layer for protecting the outermost layer may be integrally formed on the outer side of the outermost layer, thereby improving durability and the like.
[0026] Furthermore, the clad layer may have a multi-clad structure including an inner clad layer and an outer clad layer covering the outer peripheral surface of the inner clad layer and having a lower refractive index than the inner clad layer, thereby widening the total reflection angle and resulting in higher light emission.
[0027] A reflective layer may be provided on the outer side of the outermost layer or the protective layer. By reflecting the scintillation light emitted in the outermost layer or the light whose wavelength has been converted in the core on the reflective layer, the scintillation light is less likely to leak out from the side surface of the fiber, resulting in high luminescence. The reflective film may be a metal film. With this configuration, high reflectance can be obtained with a small thickness.
[0028] A method for producing a plastic scintillation fiber according to one aspect of the present invention includes the steps of: an outermost layer including a plastic material that contains an organic compound including an element having a neutron reaction cross section larger than that of hydrogen and that emits scintillation light when irradiated with a neutron beam; a high refractive index core provided inside the outermost layer and including at least one type of phosphor that absorbs the scintillation light and converts it to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, a step of inserting a second cylinder for the cladding layer into a first cylinder for the outermost layer, and inserting the core rod into the second cylinder to prepare a preform; and a step of drawing the preform while heating it.
[0029] A method for producing a plastic scintillation fiber according to one aspect of the present invention includes the steps of: an outermost layer including a plastic material that contains an organic compound including an element having a neutron reaction cross section larger than that of hydrogen and that emits scintillation light when irradiated with a neutron beam; a high refractive index core provided inside the outermost layer and including at least one type of phosphor that absorbs the scintillation light and converts it to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, The outermost layer is coated on the surface of the wavelength conversion fiber including the core and the cladding layer. Effect of the Invention
[0030] According to the present invention, it is possible to provide a plastic scintillation fiber that is capable of detecting neutron rays with higher sensitivity than conventional scintillation fibers and has excellent productivity. [Brief description of the drawings]
[0031] [Figure 1] 1 is a cross-sectional view of a plastic scintillation fiber according to a first embodiment. [Diagram 2] FIG. 4 is a cross-sectional view of a plastic scintillation fiber according to a modified example of the first embodiment. [Diagram 3] FIG. 11 is a cross-sectional view of a plastic scintillation fiber according to another modified example of the first embodiment. [Figure 4] 1 is a perspective view showing a manufacturing method of a plastic scintillation fiber according to a first embodiment. [Diagram 5] 1 is a perspective view showing an application example of a scintillation fiber according to the first embodiment. FIG. [Figure 6] The emission spectrum of para-terphenyl added to the outermost layer and the absorption and emission spectra of the wavelength conversion phosphor BBOT. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, specific embodiments to which the present invention is applied will be described in detail with reference to the drawings. However, the present invention is not limited to the following embodiments. In addition, the following description and drawings are appropriately simplified for clarity of explanation.
[0033] (Embodiment 1) <Structure of plastic scintillation fiber> A plastic scintillation fiber according to a first embodiment of the present invention will be described with reference to Fig. 1. Fig. 1 is a cross-sectional view of the plastic scintillation fiber according to the first embodiment. As shown in FIG. 1, the plastic scintillation fiber according to the first embodiment includes an outermost layer 1, a core 2, and a cladding layer 3.
[0034] The outermost layer 1 is made of a plastic material that emits scintillation light when irradiated with a neutron beam. The plastic material contains an organic compound containing an element with a neutron reaction cross section larger than that of hydrogen. The plastic material may contain a phosphor that absorbs the scintillation light emitted from the plastic material and converts it to a longer wavelength, in addition to the organic compound containing an element with a neutron reaction cross section larger than that of hydrogen.
[0035] The outermost layer 1 only needs to be sufficiently luminous and transparent so that the scintillation light can penetrate the cladding layer 3 and enter the central core 2; high transparency is not required, but it is desirable that it is as transparent as possible. The thickness of the outermost layer may be made thicker in order to obtain the required sensitivity to neutrons. Even if the outermost layer 1, which is a scintillator layer, has low transparency, long-distance transmission is possible as long as the central core 2, which is responsible for optical transmission, has high transparency.
[0036] The core 2 is provided inside the outermost layer 1, and is made of a transparent resin with a high refractive index that contains at least one type of phosphor that absorbs the scintillation light generated in the outermost layer 1 and converts it to a longer wavelength. The refractive index of the transparent resin constituting the core 2 is preferably 1.5 or more.
[0037] The cladding layer 3 covers the outer peripheral surface of the core 2 and is made of a transparent resin having a lower refractive index than the core 2. Here, the wavelength conversion fiber composed of the core 2 and the cladding layer 3 and the outermost layer 1 covering the outer peripheral surface of the wavelength conversion fiber are integrally formed. For long-distance transmission as an optical fiber, the transparency of the cladding layer 3 is as important as the transparency of the core 2. For long-distance transmission, the transparency of the outermost layer 1 is not so important.
[0038] To perform long-distance transmission as an optical fiber, the thickness of cladding layer 3 is preferably 3 μm to 100 μm, which is sufficiently thicker than the depth of the evanescent wave of the transmitted light seeping out from the core 2 into the cladding layer 3. If the thickness of cladding layer 3 is sufficiently thicker than the depth of the evanescent wave seeping out into the cladding layer 3, the cladding layer 3 and the outermost layer 1 may have the same refractive index, or may even be made of the same transparent resin.
[0039] The phosphor contained in the core 2 is preferably one whose absorption spectrum matches the wavelength of the scintillation light generated in the outermost layer 1 and whose fluorescence spectrum to be wavelength-converted is as far away from the absorption spectrum as possible. Furthermore, the core 2 may contain a second phosphor for further wavelength conversion in order to match the wavelength sensitivity of a photoelectric detector such as a photomultiplier tube (PMT) or an avalanche photodiode (APD). Details of the phosphor will be described later.
[0040] In the plastic scintillation fiber according to the first embodiment, scintillation light is generated in the outermost layer 1 in response to irradiation with neutron beams, and the scintillation light is absorbed by the inner core 2, converts its wavelength, and transmits it. Therefore, it is possible to detect neutron beams with high sensitivity, which were difficult to detect with conventional plastic scintillation fibers due to their low sensitivity. In other words, the plastic scintillation fiber according to the first embodiment is a composite plastic optical fiber that combines a scintillation function for neutron beams and a wavelength conversion function.
[0041] In addition, the wavelength conversion fiber composed of the core 2 and the cladding layer 3 and the outermost layer 1 covering the outer peripheral surface of the wavelength conversion fiber are integrally formed. Therefore, the post-processing of combining the scintillator and the wavelength conversion fiber, which was previously required, is no longer necessary, and the productivity is improved dramatically and the cost is reduced compared to the conventional method. A protective layer (not shown) for protecting the outermost layer may be integrally formed on the outer side of the outermost layer 1. The protective layer improves the durability of the plastic scintillation fiber.
[0042] <Modification of plastic scintillation fiber> Fig. 2 is a cross-sectional view of a plastic scintillation fiber according to a modified example of the first embodiment. As shown in Fig. 2, a reflective layer 5 may be provided on the surface of the outermost layer 1 or the protective layer. The scintillation light emitted by the outermost layer 1 and the light whose wavelength has been converted by the core 2 are reflected by the reflective layer 5, making them less likely to leak out from the side surface of the fiber, resulting in high light emission. Here, by making the reflective layer 5 a metal film, it is possible to obtain high reflectivity with a small thickness, which is preferable.
[0043] 3 is a cross-sectional view of a plastic scintillation fiber according to another modification of the first embodiment. The plastic scintillation fiber according to the other modification has clad layer 3 as an inner clad layer and further has clad layer 4 as an outer clad layer. That is, the clad layer has a multi-clad structure including an inner clad layer (clad layer 3) and an outer clad layer (clad layer 4). Clad layer 4 covers the outer peripheral surface of clad layer 3 and is made of a transparent resin with a lower refractive index than clad layer 3.
[0044] Here, the re-emitted light that has been wavelength-converted in core 2 is radiated isotropically in terms of solid angle within core 2. Therefore, only light within a total reflection angle based on the refractive index difference between core 2 and cladding layer 3 or cladding layer 4 can be transmitted in the fiber direction. The plastic scintillation fiber according to another modification includes cladding layer 4 with a low refractive index in addition to cladding layer 3, and therefore has a wider total reflection angle (larger numerical aperture NA) than the plastic scintillation fiber of Fig. 1, resulting in higher light emission.
[0045] <Material of outermost layer 1> The outermost layer 1, which is a scintillator layer, is made of a transparent resin, i.e., a plastic material, that emits scintillation light when irradiated with neutrons. The transparent resin contains an organic compound that includes an element with a neutron reaction cross section larger than that of hydrogen.
[0046] The transparent resin constituting the outermost layer 1 is preferably thermoplastic so that it can be drawn into a thin line by heating. As such a transparent resin, a homopolymer or copolymer made of any one of a methacrylic acid ester monomer group represented by methyl methacrylate, an acrylic acid ester monomer group represented by methyl acrylate, and an aromatic monomer group having a vinyl group represented by styrene is preferable.
[0047] Here, the transparent resin may contain a phosphor that emits scintillation light when exposed to radiation, or the transparent resin itself may emit scintillation light when exposed to radiation. As a transparent resin that itself emits scintillation light when exposed to radiation, a homopolymer or copolymer made of any one of a group of aromatic monomers having a vinyl group, typified by styrene, is preferable.
[0048] It is desirable for organic compounds containing elements with a neutron reaction cross section larger than that of hydrogen to be stable and highly soluble in aromatic monomers with vinyl groups, such as styrene (i.e., monomers that are the raw material for transparent resins). If the solubility is high, the polymer obtained by dissolving the organic compound in the aromatic monomer and polymerizing it will be highly transparent. If the solubility is low, the organic compound will not disperse uniformly in the transparent resin, causing problems such as variations in sensitivity to neutrons. Also, if the organic compound is dispersed as a powder, it may be difficult to draw a line by heating.
[0049] Elements with neutron reaction cross sections greater than that of hydrogen include lithium-6, boron-10, and gadolinium. As the organic compound containing lithium 6, lithium carboxylates such as lithium methacrylate, lithium phenylsalicylate, and lithium pivalate are preferably used.
[0050] As the organic compound containing boron 10, carborane-based compounds such as o-carborane, m-carborane, p-carborane, and derivatives thereof are preferably used. Carborane compounds (B 10 C2H 12 ) has a high ratio of boron in its molecular weight, and boron-10 atoms can be added efficiently. Here, if the ratio of the total atomic weight of boron in the molecular weight is 50 mass% or more, boron-10 can be contained at a high concentration, and neutron reactivity is increased.
[0051] As the organic compound containing gadolinium, gadolinium alkoxides such as gadolinium isopropoxide, gadolinium complexes such as tris(2,2,6,6-tetramethyl-3,5-heptanedionato)gadolinium, and the like are suitably used.
[0052] The wavelength conversion phosphor contained in the outermost layer 1 is preferably an organic phosphor having an aromatic ring and a resonant structure, and is monomolecularly dissolved in the core 2. Representative phosphors that absorb light at 250 to 350 nm include 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD), 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole (PBD), para-terphenyl (PTP), para-quaterphenyl (PQP), 2,5-diphenyloxazole (PPO), 1-phenyl-3-(2,4,6-trimethylphenyl)-2-pyrazoline (PMP), 3-hydroxyflavone (3HF), and the like.
[0053] Also preferred are 4,4'-bis-(2,5-dimethylstyryl)-diphenyl (BDB), 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT), 1,4-bis-(2-(5-phenyloxazolyl))benzene (POPOP), 1,4-bis-(4-methyl-5-phenyl-2-oxazolyl)benzene (DMPOPOP), 1,4-diphenyl-1,3-butadiene (DPB), 1,6-diphenyl-1,3,5-hexatriene (DPH), and the like, which absorb at 350 to 400 nm.
[0054] An example of the outermost layer 1 is polystyrene containing lithium pivalate as an organic compound containing an element with a neutron reaction cross section larger than that of hydrogen, and containing a phosphor that converts the scintillation light emitted by the polystyrene to a longer wavelength. Approximately 7.5% of the lithium contained in the lithium pivalate is lithium-6. Lithium-6 generates alpha rays when exposed to neutron rays. The alpha rays cause the polystyrene to emit scintillation light, which is absorbed by the phosphor and shifted to a longer wavelength before being emitted. This outermost layer 1 emits visible light of 400 to 500 nm when exposed to neutron rays.
[0055] Another example of the outermost layer 1 is polystyrene containing a carborane compound containing a high proportion of boron as an organic compound containing an element with a neutron reaction cross section larger than that of hydrogen, and containing a phosphor that converts the scintillation light of polystyrene to a long wavelength. Approximately 19.8% of the boron contained in the carborane compound is boron-10, which has a much larger neutron reaction cross section than hydrogen. Boron-10 generates alpha rays when exposed to neutron rays. The alpha rays cause polystyrene to emit scintillation light, which is absorbed by the phosphor and shifted to a long wavelength before emitting light. This outermost layer 1 emits scintillation light of 350 to 400 nm when exposed to neutron rays.
[0056] The organic compound, plastic material (transparent resin), and phosphors having a neutron reaction cross section larger than that of hydrogen are not limited to the above. The compounding ratio and concentration of the above materials are appropriately selected depending on the degree of difficulty of production, and are not limited to the above.
[0057] <Core 2 Materials> There are no restrictions on the material used for the core 2 so long as it is a transparent resin. Among them, a homopolymer or copolymer made of any one of a methacrylic acid ester monomer group represented by methyl methacrylate, an acrylic acid ester monomer group represented by methyl acrylate, and an aromatic monomer group having a vinyl group represented by styrene is preferable.
[0058] Among them, a polymer made of an aromatic monomer having a vinyl group is preferable because it has a high refractive index. The refractive index difference between the core 2 and the cladding layer 3 becomes large, and the total reflection angle becomes wide. In other words, among the light wavelength-converted in the core 2, light with a wider angle can be transmitted, resulting in a scintillation fiber with higher luminescence.
[0059] The wavelength conversion phosphor contained in the core 2 is preferably an organic phosphor having an aromatic ring and a resonant structure, and is monomolecularly dissolved in the core 2. Representative phosphors that absorb light at 250 to 350 nm include 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD), 2-(4-biphenyl)-5-phenyl-1,3,4-oxadiazole (PBD), para-terphenyl (PTP), para-quaterphenyl (PQP), 2,5-diphenyloxazole (PPO), 1-phenyl-3-(2,4,6-trimethylphenyl)-2-pyrazoline (PMP), and 3-hydroxyflavone (3HF).
[0060] Also preferred are 4,4'-bis-(2,5-dimethylstyryl)-diphenyl (BDB), 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT), 1,4-bis-(2-(5-phenyloxazolyl))benzene (POPOP), 1,4-bis-(4-methyl-5-phenyl-2-oxazolyl)benzene (DMPOPOP), 1,4-diphenyl-1,3-butadiene (DPB), 1,6-diphenyl-1,3,5-hexatriene (DPH), and the like, which absorb at 350 to 400 nm.
[0061] In order to obtain high light emission, it is preferable that the absorption spectrum of the wavelength conversion phosphor contained in the core 2 and the emission spectrum of the phosphor contained in the outermost layer 1 overlap widely. The above-mentioned wavelength conversion phosphors may be used alone, or multiple wavelength conversion phosphors may be used in combination. It is preferable that each wavelength conversion phosphor has a high quantum yield and little overlap between the absorption spectrum and the emission spectrum (a large Stokes shift). Since the longer the wavelength is, the smaller the transmission loss of visible light is, as a characteristic of plastic fibers, wavelength conversion phosphors that emit light at longer wavelengths are preferable, and two or more types may be used in combination as appropriate. It is preferable that the wavelength conversion phosphor is soluble in the transparent resin that constitutes the core 2.
[0062] The concentration of the wavelength conversion phosphor, whether it is a single one or a plurality of wavelength conversion phosphors, is preferably 50 to 10,000 ppm by mass concentration, more preferably 100 to 1,000 ppm. If the concentration is too low, the scintillation light from the outermost layer 1 cannot be efficiently absorbed in the core 2. On the other hand, if the concentration is too high, the effect of self-absorption of the phosphor itself becomes large, reducing the wavelength conversion efficiency or reducing the transmittance of the converted light, thereby worsening the attenuation length.
[0063] <Material of Clad Layer 3> There are no restrictions on the material used for the cladding layer 3, so long as it is a transparent resin having a lower refractive index than the core 2. Among them, homopolymers or copolymers made from any of the following raw materials are preferable: methacrylic acid ester monomers represented by methyl methacrylate, fluorinated monomers such as perfluoroalkyl methacrylate, and acrylic acid ester monomers represented by methyl acrylate, and fluorinated monomers such as perfluoroalkyl acrylate.
[0064] <Material of Clad Layer 4> The material used for the cladding layer 4 may be any transparent resin having a refractive index lower than that of the cladding layer 3. It may be selected from the monomer group of the cladding layer 3. In particular, it is preferable to select from a fluorine-containing monomer group having a low refractive index.
[0065] These monomers can be easily used to obtain polymers or copolymers by heat or light irradiation, and therefore have the advantage of being able to form precise compositional distributions and being easy to handle. An organic peroxide or an azo compound may be added as a polymerization initiator during polymerization. Representative organic peroxides include 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, n-butyl-4,4-bis(t-butylperoxy)valerate, and 1,1-bis(t-butylperoxy)cyclohexane, but there are no particular limitations as long as they generate radicals by heat or light irradiation.
[0066] Mercaptan may be added as a chain transfer agent to adjust the molecular weight. A typical example of mercaptan is octyl mercaptan, but there is no particular restriction as long as it has the R-SH (where R represents an organic group) structure.
[0067] <Reflective layer material> There are no restrictions on the material constituting the reflective layer 5, so long as it is a material that can reflect light emitted from the side surface of the fiber with high reflectance. Among them, a metal film can obtain high reflectance with a thinner thickness compared to, for example, white reflective paint, and is particularly preferred when a thin diameter is required for the fiber.
[0068] The metal film is not particularly limited as long as it has a high reflectance in the required wavelength range, such as aluminum, gold, silver, nickel, etc. Aluminum and silver are preferable because of their high reflectance in the visible light range. Furthermore, aluminum is preferable from the viewpoint of cost.
[0069] The thickness of the metal film is not particularly limited, but it is preferable to obtain a high reflectance in the visible light region with a thickness as thin as possible. For example, for aluminum, the thickness is preferably 10 to 100 nm, more preferably 20 to 70 nm. For silver, the thickness is preferably 35 to 150 nm, more preferably 50 to 100 nm. The film formation method is not particularly limited, and may be a vapor deposition method, a sputtering method, or the like.
[0070] <Manufacturing method of plastic scintillation fiber> 4 is a perspective view showing a manufacturing method of a plastic scintillation fiber according to the embodiment 1. FIG 4 shows a base material (preform) for manufacturing the plastic scintillation fiber shown in FIG.
[0071] The first cylinder 11 is a cylinder made of a thermoplastic resin that emits scintillation light when exposed to a neutron beam. This thermoplastic resin contains an organic compound that includes an element with a neutron reaction cross section larger than that of hydrogen. The first cylinder 11 constitutes the outermost layer 1 after drawing. An example of a manufacturing method for the first cylinder 11 will be described later in the Examples.
[0072] The rod 12 is a cylindrical body made of a transparent thermoplastic resin in which at least one type of phosphor that absorbs scintillation light and converts it to a longer wavelength is dissolved. The rod 12 constitutes the core 2 after being drawn. The second cylinder 13 is a cylinder made of a transparent thermoplastic resin and has a lower refractive index than the rod 12. The second cylinder 13 constitutes the cladding layer 3 after the drawing process.
[0073] As shown in Fig. 4, a preform is produced by inserting a second cylinder 13 into a first cylinder 11 and inserting a rod 12 into the second cylinder 13. Fig. 4 shows a state in the middle of inserting the rod 12 into the second cylinder 13. The tip of the produced preform is heated and drawn to an outer diameter of, for example, 1 mm, to obtain the plastic scintillation fiber according to the first embodiment.
[0074] As shown in FIG. 4, gaps are formed between the first cylinder 11, the second cylinder 13, and the rod 12. However, since the wire drawing process is performed under reduced pressure, the core 2, the cladding layer 3, and the outermost layer 1 are tightly adhered and integrally formed. The plastic scintillation fiber according to the modified example shown in FIG. 3 can be manufactured by the same manufacturing method.
[0075] In the manufacturing method of the plastic scintillation fiber according to the first embodiment, a scintillator layer (outermost layer 1) that emits light by neutron beams is integrally formed on the outer peripheral surface of the wavelength conversion fiber (core 2 and cladding layer 3). Therefore, the plastic scintillation fiber is capable of detecting neutron beams and transmitting light. In other words, the plastic scintillation fiber has the functions of both a conventional scintillator and a wavelength conversion fiber by itself.
[0076] Therefore, the post-processing required for combining the scintillator and wavelength conversion fiber, which was previously required, is no longer necessary, and productivity is improved and costs are reduced compared to the past. In particular, when detecting images, there is no need to separate and combine each scintillator for each wavelength conversion fiber, and it is sufficient to simply line up the plastic scintillation fibers. Therefore, productivity is dramatically improved and costs are reduced compared to the past.
[0077] After the wavelength conversion fiber (core 2 and cladding layer 3) is manufactured, the scintillator layer (outermost layer 1) may be integrally formed on the surface of the wavelength conversion fiber by coating (including painting). However, as described above, if the scintillator layer (outermost layer 1) and the wavelength conversion fiber (core 2 and cladding layer 3) are manufactured simultaneously by drawing, the productivity is further improved.
[0078] <Applications of plastic scintillation fibers> Next, an application example of the plastic scintillation fiber according to the first embodiment will be described with reference to Fig. 5. Fig. 5 is a perspective view showing an application example of the plastic scintillation fiber according to the first embodiment. In this application example, the plastic scintillation fibers PSF according to the first embodiment are arranged in an array on a substrate. Naturally, the right-handed xyz Cartesian coordinate system shown in Fig. 5 is a convenient way to explain the positional relationship of the components. Usually, the positive direction of the z axis is vertically upward, and the xy plane is a horizontal plane.
[0079] A photoelectric detector such as a photomultiplier tube (not shown) is connected to each plastic scintillation fiber PSF, and the transmitted light can be detected. With this configuration, one-dimensional image detection (position detection) with a resolution of, for example, 1 mm is possible. Here, the resolution is equal to the diameter of the plastic scintillation fiber PSF. Furthermore, if two such arrays of plastic scintillation fibers PSF are provided and arranged perpendicular to each other and stacked one on top of the other, two-dimensional image detection can also be realized.
[0080] In this way, image detection of neutron rays with high spatial resolution can be achieved easily and at low cost by using the plastic scintillation fiber according to this embodiment. EXAMPLES
[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0082] <Example 1> 5% by mass of m-carborane, an organic compound containing boron-10 whose neutron reaction cross section is larger than that of hydrogen, and 1% by mass of the phosphor 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD) were added to styrene monomer and polymerized, and the polymer was molded into a cylinder for the outermost layer (first cylinder 11 in Figure 4) with an outer diameter of 50 mm and an inner diameter of 40 mm.
[0083] A core rod (rod 12 in FIG. 4) made of polystyrene (refractive index 1.59) with a diameter of 32 mm and a cladding layer cylinder (second cylinder 13 in FIG. 4) made of polymethyl methacrylate (refractive index 1.49) with an outer diameter of 38 mm and an inner diameter of 34 mm were prepared. 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT) was dissolved in the core rod as a wavelength conversion phosphor at a concentration of 200 ppm by mass.
[0084] As shown in Fig. 4, a cylinder for cladding layer was inserted into a cylinder for the outermost layer, and a core rod was inserted into the cylinder for the cladding layer to prepare a preform. While heating the tip of this preform, it was integrally drawn under reduced pressure to an outer diameter of 1 mm, to obtain a plastic scintillation fiber according to Example 1. This plastic scintillation fiber has the cross-sectional configuration shown in Fig. 1. The outer diameter was 1000 µm, the diameter of the cladding layer 3 was 770 µm, the diameter of the core 2 was 680 µm, the thickness of the outermost layer 1 was 115 µm, and the thickness of the cladding layer 3 was 45 µm.
[0085] Fig. 6 is a graph showing the emission spectrum of the phosphor 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD) added to the outermost layer 1, and the absorption and emission spectra of the wavelength conversion phosphor BBOT added to the core 2. As shown in Fig. 6, there is a large overlap between the emission spectrum of b-PBD added to the outermost layer 1 and the absorption spectrum of BBOT added to the core 2. The plastic scintillation fiber according to Example 1 contains an organic compound with a neutron reaction cross section larger than that of hydrogen, and therefore has improved neutron sensitivity compared to conventional plastic scintillation fibers.
[0086] <Example 2> As in Example 1, a cylinder for the outermost layer (first cylinder 11 in FIG. 4) with an outer diameter of 50 mm and an inner diameter of 40 mm was molded. Also, as in Example 1, a core rod (rod 12 in FIG. 4) with a diameter of 28 mm made of polystyrene (refractive index 1.59) and a cylinder for the inner clad layer (second cylinder 13 in FIG. 4) with an outer diameter of 33 mm and an inner diameter of 30 mm made of polymethyl methacrylate (refractive index 1.49) were prepared. BBOT was dissolved in the core rod as a wavelength conversion phosphor at a concentration of 300 ppm by mass.
[0087] Furthermore, in Example 2, a cylinder for an outer clad layer (not shown) was prepared, which was made of a copolymer (refractive index 1.42) of a fluorinated monomer such as perfluoroalkyl acrylate and had an outer diameter of 38 mm and an inner diameter of 35 mm. The cylinder for the outer clad layer constitutes the clad layer 4 shown in FIG. 3 after drawing. Then, a cylinder for an outer clad layer was inserted inside the cylinder for the outermost peripheral layer, a cylinder for an inner clad layer was inserted inside that, and a core rod was inserted inside that, to prepare a preform.
[0088] While heating the tip of this preform, it was integrally drawn under reduced pressure so that the outer diameter became 1 mm, to obtain a plastic scintillation fiber according to Example 2. This plastic scintillation fiber had the cross-sectional configuration shown in Fig. 3. The outer diameter was 1000 µm, the outer diameter of cladding layer 4 was 754 µm, the outer diameter of cladding layer 3 was 682 µm, the diameter of core 2 was 612 µm, the thickness of outermost layer 1 was 123 µm, the thickness of cladding layer 4 was 36 µm, and the thickness of cladding layer 3 was 35 µm.
[0089] When a neutron beam was incident on the plastic scintillation fiber of Example 2, a light quantity about 30% higher than that of Example 1 was observed at the tip 10 m away. Although the diameter of the core 2 was smaller than that of Example 1, it is believed that the provision of the cladding layer 4 with a lower refractive index widened the total reflection angle, resulting in higher light emission.
[0090] <Example 3> 1.9 mass% of lithium pivalate, an organic compound containing lithium 6, whose neutron reaction cross section is larger than that of hydrogen, and mass% of the phosphor 2-(4-t-butylphenyl)-5-(4-biphenyl)-1,3,4-oxadiazole (b-PBD) were added to styrene monomer and polymerized, and then a cylinder for the outermost layer (first cylinder 11 in Figure 4) with an outer diameter of 50 mm and an inner diameter of 40 mm was formed.
[0091] A core rod (rod 12 in FIG. 4) made of polystyrene (refractive index 1.59) with a diameter of 32 mm and a cladding layer cylinder (second cylinder 13 in FIG. 4) made of polymethyl methacrylate (refractive index 1.49) with an outer diameter of 38 mm and an inner diameter of 34 mm were prepared. 2,5-bis-(5-t-butyl-benzoxazoyl)thiophene (BBOT) was dissolved in the core rod as a wavelength conversion phosphor at a concentration of 200 ppm by mass.
[0092] As shown in Fig. 4, a cylinder for cladding layer was inserted into a cylinder for the outermost layer, and a core rod was inserted into the cylinder for cladding layer to prepare a preform. The tip of this preform was heated and integrally drawn under reduced pressure to an outer diameter of 1 mm to obtain a plastic scintillation fiber according to Example 1. This plastic scintillation fiber has the cross-sectional configuration shown in Fig. 1. The outer diameter was 1000 µm, the diameter of the cladding layer 3 was 770 µm, the diameter of the core 2 was 680 µm, the thickness of the outermost layer 1 was 115 µm, and the thickness of the cladding layer 3 was 45 µm. The plastic scintillation fiber according to Example 3 contains an organic compound with a neutron reaction cross section larger than that of hydrogen, and therefore has improved neutron sensitivity compared to conventional plastic scintillation fibers.
[0093] <Example 4> An aluminum film was formed on the surface of the plastic scintillation fiber of Example 1 by vapor deposition to a thickness of about 50 nm. The scintillation light emitted in the outermost layer 1 and the light whose wavelength has been converted in the core 2 are reflected by the reflective layer 5, making them less likely to leak out from the side surface of the fiber, resulting in high luminescence.
[0094] The present invention is not limited to the above-described embodiment, and can be modified as appropriate without departing from the spirit and scope of the present invention.
[0095] This application claims priority based on Japanese Patent Application No. 2020-155285, filed on September 16, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0096] 1 Outermost layer 2 cores 3. Clad layer (inner clad layer) 4 Clad layer (outer clad layer) 5 reflective layer 11 First Cylinder 12 Rod 13 Second Cylinder PSF Plastic Scintillation Fiber
Claims
1. an outermost layer including a plastic material that contains an organic compound including an element having a neutron reaction cross section larger than that of hydrogen and emits scintillation light when irradiated with a neutron beam, and at least one type of first phosphor that absorbs the scintillation light and converts it to a longer wavelength; a high refractive index core provided inside the outermost layer and including at least one type of second phosphor that absorbs light emitted by the first phosphor and converts the light to a longer wavelength; a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core; a wavelength conversion fiber including the core and the cladding layer and the outermost layer covering an outer peripheral surface of the wavelength conversion fiber are integrally formed, The scintillation light absorbed by the first phosphor is ultraviolet light having a wavelength of 250 to 350 nm, The second phosphor absorbs light having a wavelength of 350 to 400 nm emitted by the first phosphor and converts it into light having a longer wavelength. Plastic scintillating fiber.
2. The organic compound contains lithium 6.
2. The plastic scintillation fiber according to claim 1.
3. The organic compound contains boron-10.
2. The plastic scintillation fiber according to claim 1.
4. The organic compound is a carborane compound.
4. The plastic scintillation fiber according to claim 3.
5. The ratio of boron to the molecular weight of the organic compound is 50% or more.
5. The plastic scintillation fiber according to claim 3 or 4.
6. The organic compound includes gadolinium.
2. The plastic scintillation fiber according to claim 1.
7. the wavelength conversion fiber and the outermost layer are integrally formed by a drawing process; The plastic scintillation fiber according to any one of claims 1 to 6.
8. A protective layer for protecting the outermost layer is integrally formed on the outer side of the outermost layer. The plastic scintillation fiber according to any one of claims 1 to 7.
9. The cladding layer is An inner clad layer; and an outer clad layer covering the outer peripheral surface of the inner clad layer and having a refractive index lower than that of the inner clad layer. The plastic scintillation fiber according to any one of claims 1 to 8.
10. A reflective layer is provided on the outer side of the outermost layer. The plastic scintillation fiber according to any one of claims 1 to 7.
11. A reflecting layer is provided on the outer side of the protective layer. The plastic scintillation fiber according to claim 8.
12. The reflective layer is a metal film.
12. The plastic scintillation fiber according to claim 10 or 11.
13. an outermost layer including a plastic material that contains an organic compound including an element having a neutron reaction cross section larger than that of hydrogen and emits scintillation light when irradiated with a neutron beam, and at least one type of first phosphor that absorbs the scintillation light and converts it to a longer wavelength; a high refractive index core provided inside the outermost layer and including at least one type of second phosphor that absorbs light emitted by the first phosphor and converts the light to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, a step of inserting a second cylinder for the cladding layer into a first cylinder for the outermost layer, and inserting the core rod into the second cylinder to prepare a preform; and a step of drawing the preform while heating it. The scintillation light absorbed by the first phosphor is ultraviolet light having a wavelength of 250 to 350 nm, The second phosphor absorbs light having a wavelength of 350 to 400 nm emitted by the first phosphor and converts it into light having a longer wavelength. A method for manufacturing plastic scintillation fibers.
14. an outermost layer including a plastic material that contains an organic compound including an element having a neutron reaction cross section larger than that of hydrogen and emits scintillation light when irradiated with a neutron beam, and at least one type of first phosphor that absorbs the scintillation light and converts it to a longer wavelength; a high refractive index core provided inside the outermost layer and including at least one type of second phosphor that absorbs light emitted by the first phosphor and converts the light to a longer wavelength; A method for manufacturing a plastic scintillation fiber comprising: a clad layer covering an outer peripheral surface of the core and having a refractive index lower than that of the core, coating the outermost layer on a surface of the wavelength conversion fiber including the core and the cladding layer; The scintillation light absorbed by the first phosphor is ultraviolet light having a wavelength of 250 to 350 nm, The second phosphor absorbs light having a wavelength of 350 to 400 nm emitted by the first phosphor and converts it into light having a longer wavelength. A method for manufacturing plastic scintillation fibers.
Citation Information
Patent Citations
Transmission device for radiation ray detection light
JP1994201835A
High-efficiency, high-resolution and real-time radiographic imaging system
JP1994317713A
Fiber type radiation detector
JP1997236669A
Radiation and neutron image detector
JP2002221578A
Pixel type two-dimensional image detector
JP2011141239A